2018
DOI: 10.1002/smr.1964
|View full text |Cite
|
Sign up to set email alerts
|

Agile practices for global software development vendors in the development of green and sustainable software

Abstract: Over the last decade, the use of agile methods has grown dramatically for software development. Agile methods guarantee to accelerate the delivery of remarkable software with increased user satisfaction and reduced cost. However, in recent years, due to emergence of green software engineering, software developers are compelled to focus more on green and sustainable aspects of software. Global software engineering aims to design, develop, and use a software with limited energy and computing resources. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 82 publications
(149 reference statements)
0
24
0
Order By: Relevance
“…Many systematic reviews have been conducted within the scope of GSD. Some of the most recent systematic literature reviews and mapping studies in this domain have identified solutions, challenges or research gaps in terms of software architecting, 10 knowledge sharing, 21–23 agile practices, 12,24 requirements risks and change management, 25–29 cultural differences 28,29 or process improvement, 30 and among others. Although some of these studies address aspects that could indirectly be related to GSD governance, none of them directly addresses governance issues.…”
Section: Related Workmentioning
confidence: 99%
“…Many systematic reviews have been conducted within the scope of GSD. Some of the most recent systematic literature reviews and mapping studies in this domain have identified solutions, challenges or research gaps in terms of software architecting, 10 knowledge sharing, 21–23 agile practices, 12,24 requirements risks and change management, 25–29 cultural differences 28,29 or process improvement, 30 and among others. Although some of these studies address aspects that could indirectly be related to GSD governance, none of them directly addresses governance issues.…”
Section: Related Workmentioning
confidence: 99%
“…The current study, evaluates the findings of the systematic literature review in the outsourcing industry. The literature highlights that similar approach was used by other researchers [3], [10], [34], [35], [36]. Fig 1, shows the proposed research method for the identification of influencing factors and their evaluation from the experts in the outsourcing industry.…”
Section: Proposed Methodologymentioning
confidence: 98%
“…Interestingly, all the identified factors through systematic literature review were evaluated and found related to offshoring decisions. We selected only 'strong influence' column for the analysis purposes, this method was also used by other researchers to analyze the survey results [11], [15], [36].…”
Section: B Empirical Investigation (Online Survey)mentioning
confidence: 99%
“…By using the online survey (questionnaire), the identified factors were evaluated by 93 outsourcing experts across the 30 countries. Previous research studies [45][46][47] employed a similar strategy for factor assessment and evaluation.…”
Section: Performing Empirical Studymentioning
confidence: 99%